Oxide Growth Mechanism on Mg AZ91 Alloy by Anodizing: Combination of Electrochemical and Ellipsometric In-Situ Measurements. Issue 14 (20th December 2017) - Zimmer, Alexandre; Veys-Renaux, Delphine; Broch, Laurent; Stein, Nicolas; Rocca, Emmanuel
Abstract : The sparking initiation during the anodizing of metals in passivating electrolytic media is highly dependent on the physico-chemical properties of the evolving dielectric interface. The present paper focuses on magnesium alloy AZ91 and describes its anodizing in KOH 3 M over the potential range 0 to 40 V by combining in situ ellipsometric and electrochemical methods. In a first step, a thin and compact MgO anodic film is formed by ionic migration with a rate of 0.4 nm V −1 . At 4 V to 5 V, the growth stresses lead to a sharp cracking of this MgO layer and the precipitation of a porous external Mg(OH)2 layer. Under this overlayer acting as a membrane, a defective MgO film grows with a higher growth rate (1.1 nm V −1 ), inducing a new passivation state. This inner MgO layer is characterized by a relatively high dielectric constant and a large thickness (100 nm at 40 V) and is probably responsible for the low dielectric breakdown voltage observed during the anodizing process of magnesium alloy.